(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2017)
This Paper utalizes Universal Expansion to derive the System Laws, rules that govern non-linear behavior. Examples of Systems are Sudoku, the Body, the Brain, and the Universe.